Effects of cognitive behavioral play therapy techniques on low self-esteem among students - Merikan Aren; Aruna Rauna Duamit (Konselor, 2020)
This study aims to determined the effects of Cognitive Behavioral Play Therapy (CBPT) techniques on low self-esteem among UNIMAS Students. More specifically, this study identified the effects of Cognitive Behavioral Play Therapy (CBPT) techniques in experimental group at pretest and posttest on low self-esteem among UNIMAS students and to identified the effects of Cognitive Behavioral Play Therapy (CBPT) techniques in control group at pretest and posttest on low self-esteem among UNIMAS students. A case study design is distributed questionnaire called as Rosenberg Self-Esteem Scale (RSES) and counselling sessions. Purposive sampling is used to get the most suitable respondents for this study. The findings of this study have revealed there were significant difference at pretest and posttest among respondents in experimental group and control group which were respondents in experimental group increased their level of self-esteem, while there were respondents decreased their level of self-esteem in control group. Counselling sessions utilizing Cognitive Behavioral Play Therapy (CBPT) techniques have increased the level of self-esteem among UNIMAS students in experimental group who attended the group counselling sessions because they have low level of self-esteem. All the dialogues that been stated by the client in the counselling sessions about their self-esteem can be related to respondents’ personality, cognitive, behavior, emotions and actions. The findings of this study have implications towards University students and counsellor. As for the university students, they gained insight, understanding and knowledge the importance of having good level of self-esteem. For the counsellor, counsellor being helpful, trusted and skillful which after utilized the CBPT techniques, they gained new skills and knowledge on that particular therapy.